Complement block coding for reduction in peak-to-average power ratio of OFDM signals. - Tao Jiang; Guangxi Zhu.
In this article a new coding scheme, complement block coding (CBC), is proposed to reduce the PAPR of OFDM signals. This method utilizes the complement bits that are added to the original information bits, which can effectively reduce the PAPR of OFDM signals with random frame size N and the coding rate R ≤ (N - k)/N, where k is a positive integer and k ≤ N/2. The performance results obtained with CBC are given and compared with that of some well known schemes, such as simple block coding, modified simple block coding, simple odd parity code, and cyclic coding, for the same purpose. The results show that at the same coding rate 3/4, CBC can achieve almost the same performance as SBC and MSBC, but with lower complexity, and the same performance can be obtained with a higher coding rate using CBC. The PAPR reductions of CBC with coding rate (N - 1)/N are almost the same as with a coding rate less than (N - 1)/N, but almost the twice as these of SOPC when N ≥ 16. Moreover, we can find that PAPR is the lowest for all block codes using CBC with coding rate 3/4. So modified CBC (MCBC) is also proposed and analyzed, combined with the subblock processing technique to make CBC effective for OFDM systems with large frame sizes. The flexibility in coding rate choice and low complexity make the proposed CBC more suitable for random frame size with high coding rate and can also provide error detection.
Keywords: OFDM signals; complement block coding; cyclic coding; error detection; odd parity code; peak-to-average power ratio; random frame size; subblock processing technique